2001
DOI: 10.1080/003655201750313315
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Proton-Pump Inhibitors as a Diagnostic Test of Gastro-oesophageal Reflux Disease in Endoscopic-negative Patients

Abstract: 60 mg lansoprazole once daily for 5 days is an easy to use method for diagnosing GORD in endoscopy-negative patients. Using 24-h oesophageal pH monitoring as the reference method, the sensitivity was relatively high, while the specificity was lower. Further studies are needed to determine how a PPI could be used as a diagnostic test in GORD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 26 publications
1
32
0
3
Order By: Relevance
“…In fact, it has been suggested that patients with a poor response to PPIs may not have GORD and therefore should not be offered further investigation or surgery. Juul-Hansen et al [11] supported this view in a Norwegian study of the efficacy of high-dose lansoprazole in reducing antacid consumption and its sensitivity as a diagnostic tool for GORD [11]. Campos et al [7], in a miultivariate analysis of factors predicting outcome after LARS, found that a good response to PPIs was a strong predictor of successful outcome.…”
supporting
confidence: 50%
“…In fact, it has been suggested that patients with a poor response to PPIs may not have GORD and therefore should not be offered further investigation or surgery. Juul-Hansen et al [11] supported this view in a Norwegian study of the efficacy of high-dose lansoprazole in reducing antacid consumption and its sensitivity as a diagnostic tool for GORD [11]. Campos et al [7], in a miultivariate analysis of factors predicting outcome after LARS, found that a good response to PPIs was a strong predictor of successful outcome.…”
supporting
confidence: 50%
“…This questionnaire, however, includes questions about the effects of antacids, which are not prescribed in clinical practice in Japan, and a total of 26 sections of questions have to be answered, which can be inconvenient. On the other hand, heartburn and waterbrash are typical symptoms of GERD, [9][10][11] have a high specifi city for GERD, 12 and also indicate GERD severity. In this study, we used a questionnaire defi ning NERD as heartburn and waterbrash symptoms twice or more per week even if no mucosal break was seen on endoscopic examination.…”
Section: Discussionmentioning
confidence: 97%
“…Questionnaires and symptom records were used in most studies for the assessment of PPI response; although the symptom response threshold varied according to the study, in comparison with the beginning of the test, a 50%-75% recovery in symptoms was acceptable. A significant difference was not detected among PPIs in terms of effectiveness (10-12).Although the sensitivity of the PPI test is 27%-89% in patients with typical symptoms of GERD, its specificity is 35%-83% (2,(4)(5)(6)(7)(8)13,14). Because of the use of different methods and populations in studies, it is quite difficult to make comparisons.…”
mentioning
confidence: 98%
“…Although the sensitivity of the PPI test is 27%-89% in patients with typical symptoms of GERD, its specificity is 35%-83% (2,(4)(5)(6)(7)(8)13,14). Because of the use of different methods and populations in studies, it is quite difficult to make comparisons.…”
mentioning
confidence: 99%
See 1 more Smart Citation